Embryonal Carcinoma of the Pineal Gland Developed in an Adolescent Boy with Klinefelter Syndrome - Hyo Jin Choi; Eun Ah Kim; Jae Min Lee; Kyung Mi Jang; Joon Hyuk Choi (The Korean Society of Pediatric Hematology-Oncology, 2019)
Klinefelter syndrome (KS) is characterized by small testes, gynecomastia, tall stature, and hypergonadotropic hypogonadism. This condition is associated with extra X chromosomes. It is well known that these aneuploidies predispose individuals to the development of several cancers. Moreover, there are many case reports that show KS patients to have a higher relative risk for the development of malignancy. However, incracranial germ cell tumor (ICGCT) associated with KS is very uncommon. Herein, we report delayed diagnosis of KS in a 15-year-old boy with ICGCT, embryonal carcinoma of the pineal gland, after multimodality treatment in Korea.